Exploring the decision making process of women offered termination of pregnancy for serious congenital abnormality - Malope, Malebo Felicia (Division of Human Genetics, 2018)
Background: A weekly pregnancy counselling clinic is held in conjunction with foetal medicine experts at Groote Schuur Hospital for women with pregnancies complicated by foetal anomalies. In cases with poor prognoses, termination of pregnancy (TOP) may be offered. The women receive genetic counselling where the ultrasound findings, invasive testing and TOP options are discussed. Decision-making is the focus of these sessions. The experiences and decision-making processes of the women in this clinic are poorly understood, therefore this project aims to explore these women's experiences and what factors influence their decision-making regarding TOP. Methods: Qualitative research, drawing on principles of phenomenology was used as the study design. The sample for this study are women who had a prenatal diagnosis of a serious congenital abnormality and were offered TOP. The women were identified using the Division of Human Genetics pregnancy counselling database at the University of Cape Town in South Africa. Semistructured face-to-face interviews with open-ended questions were used to collect the data and close-ended questions were used to obtain the demographic data. The interviews were recorded and transcribed verbatim. The data were analysed using a thematic data analysis approach. A total of 12 women were interviewed. Results: Five themes were identified in this study. These include "Health care services", "Home", "Being a woman", "Finding meaning", and "The aftermath". The healthcare services impacted the manner in which the women made sense of the ultrasound findings. Support (or lack of) from family and the community impacted on their decision-making. Stigma attached to having a child with a disability and/or stigma against TOP and partner relationships played a role. The women questioned their role as a woman and obligations of child-bearing. Finding meaning for the event was important and this process continued until after the delivery or after the child was born. Following the event having a burial and giving away the child's clothes were found to play a significant role in their adjustment. Discussion and Conclusion: The decision-making process was multifaceted and unique to each woman. They consulted their families, partners and community but in the end they made the final decision. The women considered a multitude of factors but it seems that there may be one deciding factor. This in depth exploration of the women's experiences has provided valuable insight into the decision-making process, which can be used to improve the services offered to patients.